1974
DOI: 10.1002/dev.420070602
|View full text |Cite
|
Sign up to set email alerts
|

Critical periods in the organization of systems

Abstract: The general theory of critical periods applies to organizational processes involved in the development of any living system on any level of organization and states that the time during which an organizational process is proceeding most rapidly is the time when the process may most easily be altered or modified. Complex organizational processes involving 2 or more interdependent subprocesses may show 1 to several critical periods, depending on the time relationships of the subprocesses. The nature of the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The former happens within the first 2 weeks after birth, which possibly reflects intrinsic growth programs for the initiation of brain functions. The latter happens afterward during the critical period of primary socialization or experience-related learning (Scott et al, 1974). In agreement with this study, our study also indicates two modes of morphological changes of TTL5 cells in the somatosensory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The former happens within the first 2 weeks after birth, which possibly reflects intrinsic growth programs for the initiation of brain functions. The latter happens afterward during the critical period of primary socialization or experience-related learning (Scott et al, 1974). In agreement with this study, our study also indicates two modes of morphological changes of TTL5 cells in the somatosensory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…It is in this stage that organizational modifications occur. 33 However, it has been observed that a series of important processes involving organizational development of the nervous system also occur during adolescence. 34 During this period, sex steroids produce a structural remodelling of the circuits that determine the behavioral response to hormonal or sensory stimuli in adulthood.…”
Section: Current Evidence Of the Effects Exerted By Gonadal Steroid Hmentioning
confidence: 99%
“…Multiple sensitive periods exist for the organization of the brain and nervous system, primarily occurring during periods of rapid developmental changes (Scott et al, 1974). One of the most well-studied and best-characterized periods is that of the perinatal period in rodents.…”
Section: Puberty and Adolescencementioning
confidence: 99%